2019
DOI: 10.1017/s095026881900089x
|View full text |Cite
|
Sign up to set email alerts
|

HIV transmission between spouses living in Lu'an city, Anhui province, China: a longitudinal study

Abstract: This study aims to investigate the human immunodeficiency virus (HIV) transmission rate in HIV serodiscordant couples, in addition to the relevant influencing factors. From January 1999 to August 2016, patients with HIV/AIDS (index cases) along with their fixed partners were registered and monitored to determine the rate of HIV transmission between couples, as well as relevant influencing factors. A total of 231 HIV-positive couples were investigated, of these, 45-negative (19.48%) partners were infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(57 citation statements)
references
References 24 publications
4
53
0
Order By: Relevance
“…We also confirmed the previous evidence that patients aged old and having high-plasma HIV viral load might have a higher risk of HIV transmission ( 26 , 27 ). Older couples were usually poorly educated and lack sufficient knowledge and awareness of HIV prevention.…”
Section: Discussionsupporting
confidence: 91%
“…We also confirmed the previous evidence that patients aged old and having high-plasma HIV viral load might have a higher risk of HIV transmission ( 26 , 27 ). Older couples were usually poorly educated and lack sufficient knowledge and awareness of HIV prevention.…”
Section: Discussionsupporting
confidence: 91%
“…Most participants were heterosexual and homosexual, and among those who had a steady partner, a portion was serodiscordant. Research has shown that among PLHIV with a fixed partnership, seroconcordant companions are more common than serodiscordant (36) , and when the partner's serology is unknown the HIV transmission may be greater compared to the situation in which the partner's seropositivity is known (37) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PLHIV with a serodiscordant partner and time of diagnosis of 5 to 10 years had more inadequate adherence to ART. Studies show that ART reduces the risk of HIV transmission among serodiscordant couples (38)(39) , and interventions in this group are needed to improve adherence to ART, as well as condom use, to reduce the spread of HIV (37) . Research also found that PLHIV with a diagnosis time greater than 10 years had better adherence to antiretrovirals (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Our longitudinal genetic network study in Guangxi from 2015 to 2018 indicated that ART reduced the risk of HIV transmission by 33% at a population level. Previous studies mainly using traditional epidemiological methods have indicated that ART can reduce the risk of HIV transmission among serodiscordant couples ( Eshleman et al, 2017 ; Ma et al, 2019 ). The HPTN 071 clinic trial also confirmed the effect of ART in reducing HIV transmission at the population level ( Hayes et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%